(untitled) (Journal of Education and Development, 2021)
Strengthening the cultivation of college students’ innovation and entrepreneurial ability is not only the urgent need of the construction of national innovation system, but also the need to adapt to social development, alleviate employment pressure and cultivate innovative talents. Taking Taizhou College of Nanjing Normal University as an example, through the investigation of the influencing factors of College students’ innovation and entrepreneurial ability and the situation of College students’ innovation and entrepreneurial ability, the research group understands the current situation of College students’ innovation and entrepreneurship education, and analyzes the key factors affecting college students’ innovation and entrepreneurial ability, Finally, it puts forward some suggestions and measures to improve the innovation and entrepreneurial ability of college students.